The Role of Artificial Intelligence in Islamic Education for Inclusive Children - Anandal, Fadhia; Dartim, Dartim; Yusutria, Yusutria (Universitas Muhammadiyah Surakarta, 2024)
Artificial Intelligence (AI) is seen as a breakthrough in the world of education. This has led many teachers, especially Islamic Religious Education teachers, to start collaborating their teaching materials with sophisticated technology. This study aims to determine how artificial intelligence can be a breakthrough in creating an inclusive, comfortable and easily accessible learning environment for people with disabilities in Islamic religious education learning. The study used a qualitative descriptive literature review, with data collection through literature studies. The results of the study show that artificial intelligence can help teachers achieve the goals of Islamic religious education by instilling moral and character values. Artificial Intelligence has important implications for the development of innovative and effective learning methods in Islamic religious education. The use of artificial intelligence makes learning more interactive, allows learning to be tailored to students' needs, improves understanding of Islamic religious concepts and students' motivation in practicing character values.